Pyoderma gangrenosum and chronic osteomyelitis: a rare association - Vázquez, Fernando Javier; Oria, Inés; Saucedo, Carla; Freue, Julián; Aguera, Darío (Revista del Hospital Italiano de Buenos Aires, 2009)
.